Efficient Blue Phosphorescence in Gold(I)‐Acetylide Functionalized Coinage Metal Bis(amidinate) Complexes. Issue 70 (19th October 2020) - Feuerstein, Thomas J.; Seifert, Tim P.; Jung, André P.; Müller, Rouven; Lebedkin, Sergei; Kappes, Manfred M.; Roesky, Peter W.
Abstract: The synthesis of linear symmetric ethynyl‐ and acetylide‐amidinates of the coinage metals is presented. Starting with the desilylation of the complexes [Me3 SiC≡CC(NDipp)2 2 M2 ] (Dipp=2, 6‐diisopropylphenyl) (M=Cu, Au) it is demonstrated that this compound class is suitable to serve as a versatile metalloligand. Deprotonation with n ‐butyllithium and subsequent salt metathesis reactions yield symmetric tetranuclear gold(I) acetylide complexes of the form [(PPh3 )AuC≡CC(NDipp)2 2 M2 ] (M=Cu, Au). The corresponding Ag complex [(PPh3 )AuC≡CC(NDipp)2 2 Ag2 ] was obtained by a different route via metal rearrangement. All compounds show bright blue or blue‐green microsecond long phosphorescence in the solid state, hence their photophysical properties were thoroughly investigated in a temperature range of 20–295 K. Emission quantum yields of up to 41 % at room temperature were determined. Furthermore, similar emissions with quantum yields of 15 % were observed for the two most brightly luminescent complexes in thf solution. Abstract : Two plus two is four : The synthesis of linear symmetric ethynyl‐ and acetylide‐amidinates of the coinage metals is presented. Their photophysical properties were thoroughly investigated in a temperature range of 20–295 K. Short lifetimes and quantum yields of up to 41 % were determined. Furthermore, the complexes show pronounced PL in thf solution as well.